Cultural violence, stigma and the legacy of the anti-sealing movement - Burke, Danita Catherine ([Place of publication not identified] : ROUTLEDGE, 2023)
This book injects nuance into the debate about the moral legitimacy of environmental and animal activism and explores how activism can lead to stigma and destruction of minority group identities, cultural practices and community structures. It takes readers back to ground zero of the anti-sealing movement - Newfoundland and Labrador. This book sheds light on the human costs of activists and the repercussions for vulnerable people when activism normalizes forms of violence as acceptable to achieve their desired outcomes. Inspired by Greenpeace Canada's apology to Canadian Inuit, Indigenous and coastal peoples, this book brings into focus the local peoples who were targeted by activists and media outlets and left behind once the cultural and economic structures of the sealing industry and sealing practices were severely damaged by activist stigmatization and the global outcry against rural and coastal peoples and their practices. Drawing upon literature on cultural violence and archival research, this book will be of interest to scholars and researchers of international relations, development studies, public policy, sustainability studies and Indigenous studies.
Keywords: Sealing -- Social aspects -- Newfoundland and Labrador; Animal welfare -- Social aspects -- Newfoundland and Labrador; NATURE / Environmental Conservation & Protection; POLITICAL SCIENCE / Public Policy / Environmental Policy; SOCIAL SCIENCE / General